PENGARUH MODEL PICTURE AND PICTURE TERHADAP KETERAMPILAN MENULIS PUISI SISWA KELAS III SEKOLAH DASAR - Ripena, Ripena; Salimi, Asmayani; Kaswari, Kaswari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractIn learning to write poetry in class III of Public Elementary School 09 Southeast Pontianak, students 'understanding of learning material was not maximized, thus influencing students' writing skills especially in poetry writing skills. In addition, the lack of training in poetry writing results in low skills and student learning outcomes in Indonesian subjects so that it requires an innovative and fun learning model. One of the learning models that have been proven to support students' skills in writing poetry is to use the picture and picture model. The problem in this study is